Efektivitas Latihan Keterampilan Psikologis bagi Atlet Voli dalam Meningkatkan Kemampuan dan Membentuk Karakter (Kepribadian) - Muhammad Arja Bahauddin; Febby Alfu Khoirun Nissa; Riska Devi Kurniawati; Soni Sulistyarto; Muhammad Muhammad (Jurnal Porkes, 2026)
This research problem in volleyball requires quick decision-making and solid teamwork, but many training programs still focus on physical and technical aspects, neglecting the development of structured psychological skills integrated with character building. This study aims to test the effectiveness of structured psychological skills training (PKP) in improving mental readiness, performance-related abilities, and character building in volleyball athletes. A total of 38 volleyball athletes participated in an eight-week PS program (three times/week) that included visualization, stress management, and goal setting. A quantitative experimental design was used with pre-test and post-test measurements using a modified Psychological Skills Inventory for Sports (PSIS). Data analysis used the Wilcoxon test and Spearman's correlation. The results of the study showed a significant increase in motivation, self-confidence, mental preparation, and emphasis on teamwork (p < 0.05). In addition, a significant positive correlation was found between intelligence and mental preparation (p=0.021), as well as cooperation and self-confidence (p=0.029). These improvements indicate that psychological interventions are effective in strengthening the cognitive-motivational aspects of athletes. The relationship between intelligence and cooperation with psychological skills confirms that cognitive abilities and social character contribute to athletes' mental toughness. In conclusion, structured PKP has been proven effective in improving the mental readiness and collaborative character of volleyball athletes. The systematic integration of psychological training into athlete development programs is highly recommended.